Simulação numérica do comportamento de vigas e pilares de concreto armado via MEF usando o codigo CASTEM 2000 - Marques da Costa Jacomassi, Luciana [UNESP]; Pinto Barbosa, Monica [UNESP]; Gamino, Andre Luis (My University, 2009)
The objective of this paper is the numerical study of the behavior of reinforced concrete beams and columns by non-linear numerical simulations. The numerical analysis is based on the finite element method implemented in CASTEM 2000. This program uses the constitutive elastoplastic perfect model for the steel, the Drucker-Prager model for the concrete and the Newton-Raphson for the solution of non-linear systems. This work concentrates on the determination of equilibrium curves to the beams and force-strain curves to the columns. The numeric responses are confronted with experimental results found in the literature in order to check the reliability of the numerical analyses. © Universitat Politècnica de Catalunya (España).
Numerical simulation of the behavior of the behavior of reinforced concrete beams and columns by FEM CAASTEM 2000 program
Keywords: FEM; Non-linear analysis; R/C beams; R/C columns